Alcohol and the fetus in the west of Scotland. - Beattie, J O (1983)
Forty children with the fetal alcohol syndrome were identified in the west of Scotland. All were growth retarded and had abnormal facial features, and all those who were tested were found to have neurological or developmental abnormalities. Two children died of associated physical defects. Most of the mothers were socially deprived, and all had drunk heavily while pregnant. Three women had subsequently died. These findings provide clear evidence that in the west of Scotland maternal alcohol abuse during pregnancy is a significant cause of morbidity and mortality in children.